Evaluation of Matrix Acidizing Using Formation Water Parameters in Hilal Well, Arqom Field, Indonesia - Irmaya, Aisyah Indah; Wulandari, Sari; Ismail, Thoriq Miftahul Chair (Journal of Geoscience, Engineering, Environment, and Technology, 2026)
Formation damage due to scale deposition is a common production problem that reduces reservoir permeability and decreases oil and gas well productivity. One effective remediation technique is matrix acidizing. This study evaluates the effectiveness of matrix acidizing in a sandstone reservoir with carbonate mineral content in Hilal well, Arqom Field, by analyzing production rate changes and formation water characteristics before and after treatment. Formation water analysis plays a critical role in evaluating acid compatibility and revealing mineral dissolution mechanisms during the treatment. The Stiff method was used to characterize formation water, followed by matrix acidizing planning through optimal injection volume and pressure calculations. The treatment involved preflush, main acid injection, and displacement, along with an Injectivity Rate Test (IRT). The effectiveness was evaluated using Productivity Index (PI) and Inflow Performance Relationship (IPR) analysis. The results demonstrate that matrix acidizing significantly increased the PI of Hilal well from 1.62 bbl/psi to 3.15 bbl/psi, resulting in a 102% increase in production. Key technical parameters, including formation breakdown pressure (BHFP), acid hydrostatic pressure (pH), and surface treating pressure (STP), aligned with the designed injection volume of 46 bbl. These results demonstrate that matrix acidizing is an effective method for enhancing well productivity.